Development and performance of balck sigatoka-resistant tetraploid hybrids of plantain (Musa spp., AAB group) - Vuylsteke, D.R.; Swennen, R.L.; Ortiz, R. (1992)
A strategy to control the black sigatoka disease (Mycosphaerella fijiensis Morelet) of plantain (Musa ssp., AAB grou) in Africa, targeting the incorporation of durable host plant resistance, was initiated at the International Institute of Tropical Agriculture (IITA). The commonly accepted intractability of plantain to genetic improvement has been challenged by the identification of 37 different, seed-fertile plantain cultivars and by the production of 250 hybrids in four years of breeding work. Twenty tetraploid hybrids have been selected for their increased black sigatoka resistance, high yields, large parthenocarpic fruits and improved ratooning. ‘Calcutta 4’ (Musa acuminata spp. burmannicoides) was the diploid male parent of 17 of the selected hybrids, which indicates that the inferior bunch characteristics of this wild banana were generally not transmitted to its tetraploid progenies. Conversely, the 4x progeny of plantain readily expressed black sigatoka resistance when crossed with ‘Calcutta 4’. Progenies of the triploid plantain cvs. ‘Obino l'Ewai’ and ‘Bobby Tannap’ differed in their black sigatoka breeding values, the former producing larger numbers of promising hybrids. Tetraploids obtained from crosses of plantain cultivars with the homozygous ‘Calcutta 4’ displayed variation in black sigatoka reaction, qualitative morphological traits and growth and yield parameters, suggesting the occurrence of segregation and recombination during the modified megasporogenesis leading to the formation of 2n eggs in the triploid female plantain parents. The variation in black sigatoka reaction among the tetraploid progenies of plantain suggests that resistance could be regulated by recessive, additive genes.